Updates on thrombotic events associated with multiple myeloma. Issue 5 (4th May 2019) - Fotiou, Despina; Gavriatopoulou, Maria; Ntanasis-Stathopoulos, Ioannis; Migkou, Magdalini; Dimopoulos, Meletios A.; Terpos, Evangelos
ABSTRACT: Introduction : Despite the implementation of thromboprophylaxis guidelines, the risk of venous thromboembolism (VTE) in patients with Multiple Myeloma (MM) remains significant. There is, therefore, a need for more sensitive risk stratification tools and optimization of our thromboprophylaxis approach. Areas covered : Since 2015 there have been no breakthrough data in this field. This review aims to cover recent data that have evaluated the effectiveness and extent to which IMWG 2014 guidelines are being applied. In addition, new data on the identification of potential biomarkers of coagulation that reflect the procoagulant processes that take place in these patients and are associated with increased VTE risk will be presented. Recent developments of clinical scores that aim to effectively risk stratify MM patients and guide thromboprophylaxis will be discussed. Finally, new data on the use of direct oral anticoagulants (DOACs) in the context of thrombosis prevention in MM patients will be covered. Expert opinion : There is an ever-increasing need for a Risk assessment model that combines weighted clinical factors with biomarkers of coagulation that can sensitively risk stratify MM patients and guide management of VTE prevention which will also include Direct oral anticoagulants as data from ongoing clinical trials are much anticipated.